Too Much of a Good Thing? Telework Intensity and Workplace Experiences - Eline Moens; Louis Lippens; Kathleen Vangronsvelt; Ans De Vos; Stijn Baert (Institute of Labor Economics (IZA), 2025)
At a time when numerous organisations are urging a return to the office while many employees prefer to continue teleworking, it is crucial to ascertain the optimal level of telework intensity. In the present study, we determine this ideal level with respect to self-rated employee attitudes, behaviour, well-being, social relations and professional growth. Drawing on a five-wave longitudinal dataset, we apply fixed effects regression analyses to investigate associations between telework intensity and various dimensions of workplace experience. We offer more robust empirical evidence for favouring hybrid work schedules over an office-only or telework-only regime owing to significant advances in causal interpretation of linear and non-linear associations compared to the majority of existing studies that examine linear associations based on cross-sectional data. Our results point toward an inverted U-shaped association between telework intensity and self-rated job satisfaction, work-life balance, relationships with colleagues and professional development, with optimal levels peaking around 50% teleworking. For task efficiency and work concentration, the association appears to be concave with a plateau, stabilising at teleworking levels above 70%. Only between telework intensity and employer connectedness do we observe a slightly negative linear association.
Keywords: I31; J24; J28; J32; J81; M51; 330; telework intensity; workplace experience; hybrid work schedules; longitudinal